2019
DOI: 10.1159/000496456
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Music Therapy in Frail Elderlies: Controlled Crossover Study

Abstract: Background: Music therapy (MT) may exert beneficial preventive effects in frail elderly individuals in psychophysiological health. Objectives: One hundred and fifteen frail elderly individuals (65–89 years old) participated. Methods: Subjects were randomly divided into 2 groups for a controlled crossover trial. The MT-first group participated in group sessions of 45–50 min conducted by a certified music therapist for 12 weeks, followed by a 12-week waiting period. The waiting-first group participated in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…Assessment of physical and psychological condition through medical evaluation or tests such as General Health Questionnaire (GHQ) ( 43 ), Medical Outcomes Study 36-item Short-Form Health Survey (SF-36) ( 44 ), Instrumental Activity of Daily Living (IADL) ( 45 ), Patient Health Questionnaire (PHQ) ( 46 ), and State-Trait Anxiety Inventory (STAI) ( 47 ). These evaluations can be applied in the inclusion and exclusion of subject; moreover, if performed after experimental procedures or as part of them, they could be considered as a source of information that might be susceptible to analysis as a response to stimuli or experimental procedures.…”
Section: Experimental Designmentioning
confidence: 99%
“…Assessment of physical and psychological condition through medical evaluation or tests such as General Health Questionnaire (GHQ) ( 43 ), Medical Outcomes Study 36-item Short-Form Health Survey (SF-36) ( 44 ), Instrumental Activity of Daily Living (IADL) ( 45 ), Patient Health Questionnaire (PHQ) ( 46 ), and State-Trait Anxiety Inventory (STAI) ( 47 ). These evaluations can be applied in the inclusion and exclusion of subject; moreover, if performed after experimental procedures or as part of them, they could be considered as a source of information that might be susceptible to analysis as a response to stimuli or experimental procedures.…”
Section: Experimental Designmentioning
confidence: 99%
“…Benzer şekilde çalışma kapsamında incelenen tezlerde uyku sorunun çözümü için müzik terapisi, ışık tedavisi ve masaj uygulandığı ve sonuçlarının etkili olduğu görülmektedir 26,30 . Yaşlıların karşılaştığı diğer sorunların arasında yüksek kan basıncı, ortopedi ameliyatları sonrası ağrı gibi fizyolojik sorunlar ile anksiyete, yalnızlık gibi psikolojik sorunların olduğu ve bu sorunlarla baş etmede müzik terapisinin geniş bir yelpazede kullanıldığı ve etkili olduğu belirtilmektedir [52][53][54][55] . İncelenen tezlerde de farmakolojik olmayan yöntemler arasında en fazla kullanılan yöntemin müzik terapisi olduğu ve müzik terapisinin kan basıncı, solunum, nabız, oksijen saturasyonu, anksiyete, ajitasyon; konfor ve yalnızlık düzeyine vb.…”
Section: Araştırmaya Dahil Edilmeme öLçütleriunclassified
“…In the care for people with dementia or chronic psychiatric disorders, there has been an increased use of various forms of art, such as theatre [9], painting, drawing, singing, dance or sculpture [10,11], music [12,13], and visiting museums [14]. Positive effects were found on different quality of life aspects [9,12,15]. One study found improvement in cognition or decreased apathy or depression [11].…”
Section: Introductionmentioning
confidence: 99%